USE OF CANNABIDIOL IN THE PREVENTION OF POSTOPERATIVE COMPLICATIONS AFTER THIRD MOLAR EXTRACTIONS - Teixeira, Natalia Rosa; Vieira Junior, Reginaldo Conceição; Ferrari, Franciely; Dias, Marcelo Magalhães; de Sousa, Gabrielle Oliveira; Veloso, Cristiano; de Sousa, Lizandra Cristina Oriel; Soares, Adriana do Paço; Teixeira, Karina Imaculada Rosa; Rapozo, Raquel Helena Rodrigues; Magalhães, Wilker de Castro; Martins, Eduardo J. M.; et al. (Seven Editora, 2026)
Third molar extraction is among the most frequently performed procedures in Oral and Maxillofacial Surgery and is commonly associated with postoperative complications such as pain, edema, trismus, and functional limitation. In this context, cannabidiol (CBD) has attracted growing scientific interest due to its analgesic, anti-inflammatory, and endocannabinoid system-modulating properties, emerging as a potential therapeutic alternative for postoperative management in oral surgery. This study aimed to analyze, through an integrative literature review, the current scientific evidence regarding the use of cannabidiol in the prevention and control of postoperative complications associated with third molar extractions. The methodological framework was based on the stages proposed by Whittemore and Knafl (2005). The bibliographic search was conducted in the PubMed/MEDLINE, Scopus, Web of Science, and SciELO databases, considering studies published between 2015 and 2025 in English, Portuguese, and Spanish. Clinical trials, systematic reviews, observational studies, and experimental research related to the use of CBD in orofacial pain, inflammation, and oral surgery were included. The findings demonstrated that cannabidiol presents relevant analgesic and anti-inflammatory potential by modulating nociception and inflammatory responses through mechanisms associated with CB1 and CB2 receptors, in addition to reducing pro-inflammatory cytokines and nociceptive sensitization. Clinical studies reported reduction of postoperative pain, functional improvement, and possible reduction in the need for conventional analgesics. However, important methodological limitations remain, including heterogeneity among therapeutic protocols, differences in dosage and routes of administration, small sample sizes, and lack of clinical standardization. It is concluded that cannabidiol demonstrates promising therapeutic potential in the prevention and control of postoperative complications following third molar extractions, although further robust and standardized clinical studies are still required to consolidate its applicability in contemporary dental practice.